전악 발치 환자에서 캠퍼그나 트레이를 적용한 즉시의치 수복 증례 - 김남훈; 김종은; 오경철; 정문규; 문홍석; Kim, Nam-Hoon; Kim, Jong-Eun; Oh, Kyung Chul; Chung, Moon-Kyu; Moon, Hong-Seok (Taehan Chikwa Poch'ol Hakhoe chi, 2017)
An immediate complete denture is considered as restoration for lost natural teeth, which is fabricated following the extraction of the remaining teeth. Current esthetics and function can be retained by using immediate denture without edentulous period. However, the major disadvantages of immediate denture relate to the difficulties associated with taking accurate definitive impression and predicting the results of immediate denture. In this case report, the Campagna tray technique was used to take the final impression in a 49-year-old male patient presented with all remaining teeth diagnosed as hopeless teeth. Surgical templates were used for alveoloplasty after extraction. The immediate complete dentures were then delivered. The clinical assessments of immediate dentures showed good esthetic and functional outcomes. The patient showed high level of satisfaction. 잔존 자연치의 발치가 필요한 환자에서 즉시의치의 제작을 고려해 볼 수 있다. 즉시의치를 장착함으로써 환자가 무치악으로 지내는 기간 없이 심미 및 기능을 회복해줄 수 있는 장점이 있지만 인상 채득이 어렵다는 점, 장착 후의 결과를 예측하기 어렵다는 단점이 있다. 본 증례에서는 잔존 자연치를 모두 발치해야 하는 49세 남환에서 캠퍼그나 트레이를 이용하여 최종 인상을 채득하고 수술용 형판을 이용하여 발치 및 치조골 성형술을 시행한 후, 즉시의치를 제작 및 장착하여 심미적, 기능적으로 만족할 만한 치료 결과를 보였기에 이를 보고하고자 한다.